2011
DOI: 10.4028/www.scientific.net/amr.332-334.2153
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Oily Waste Water Using Nano-TiO<sub>2</sub>

Abstract: Photocatalytic degradation of oily wastewater using Nano-TiO2 was studied.First Nano-TiO2 powder with photocatalytic activity were prepared by sol-gel progress.Second the photo-degradation of oily wastewater on titanium dioxide was investigated.The reaction also features the photocatalytic activity of Nano-TiO2. Finally, the mechanisms of photo-oxidation were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…For studying the role of photocatalysts in degradation of oil-contaminated water, Zhang et al 67 used a photocatalytic reactor system to conduct the photodegradation experiment. The authors demonstrated that when the calcination temperature exceeded 400 °C, some of the anatase TiO 2 particles transformed into the rutile phase, which has poor photocatalytic properties, leading to a significant decrease in the photocatalytic activity of nano-TiO 2 .…”
Section: Oil Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…For studying the role of photocatalysts in degradation of oil-contaminated water, Zhang et al 67 used a photocatalytic reactor system to conduct the photodegradation experiment. The authors demonstrated that when the calcination temperature exceeded 400 °C, some of the anatase TiO 2 particles transformed into the rutile phase, which has poor photocatalytic properties, leading to a significant decrease in the photocatalytic activity of nano-TiO 2 .…”
Section: Oil Photochemistrymentioning
confidence: 99%
“…However, the UV radiation used in this study includes regions outside of the solar spectrum. Zhang et al 67 utilized UV radiation to investigate the photodegradation of oily wastewater in the presence of nano-TiO 2 with the use of a 500 W mercury lamp. To keep the lamp cool, it was housed inside a quartz tube and surrounded by a circulating water jacket.…”
Section: Photooxidation Process and Laboratory Simulation Techniquesmentioning
confidence: 99%